Organisational Commitment: Investigating the Stimulus of Organisational Justice - Lal , Dr. Bhajan (International Journal of Psychosocial Rehabilitation, 2020)
Employees play an imperative role in organisational sustainability. Therefore, an organisation must understand employees' emotions, attitudes, and behavior. Organisational Commitment empowers employees to perform the task with full passion inline with organisational goals. That is why organisational justice is considered one of the key determinants of organisational commitment. Because justice perception of employees creates a positive or negative attitude. Employee perception of justice and commitment plays a decisive role in organisational development. Considering all facts present study aims to investigate the influences of organisational justice and its dimensions (distributive, procedural,and interactional justice) on organisational comiitment. A total of 325 responses were analysed, and our obtained results suggested that organisational justice and its dimension have a significant positive impact on organisational commitment. The present study is cross-sectional. The author also provides the future direction of the research as well.